Cement-Based Renders Manufactured with Phase-Change Materials: Applications and Feasibility - Luigi Coppola; Denny Coffetti; Sergio Lorenzi (Advances in Materials Science and Engineering)
The paper focuses on the evaluation of the rheological and mechanical performances of cement-based renders manufactured with phase-change materials (PCM) in form of microencapsulated paraffin for innovative and ecofriendly residential buildings. Specifically, cement-based renders were manufactured by incorporating different amount of paraffin microcapsules—ranging from 5% to 20% by weight with respect to binder. Specific mass, entrained or entrapped air, and setting time were evaluated on fresh mortars. Compressive strength was measured over time to evaluate the effect of the PCM addition on the hydration kinetics of cement. Drying shrinkage was also evaluated. Experimental results confirmed that the compressive strength decreases as the amount of PCM increases. Furthermore, the higher the PCM content, the higher the drying shrinkage. The results confirm the possibility of manufacturing cement-based renders containing up to 20% by weight of PCM microcapsules with respect to binder.